2012
DOI: 10.1177/0093854811432421
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Alternatives for Justice-Involved Individuals with Severe Mental Illness

Abstract: Community-based alternatives to conviction and imprisonment for adult offenders with severe mental illness are receiving increasing attention from researchers and policy makers. After discussing the justifications that have been offered in support of community-based alternatives, this article reviews the current empirical evidence relevant to such alternatives. The authors use the sequential intercept model as a guide and summarize the existing research at several points along the criminal justice continuum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Interviews with officers revealed that they frequently self-select into CIT training because of prior experience with someone who had mental illness (Cross et al, 2014;Wood & Watson, 2017) or they believed they would benefit from having the enhanced skills as a response to the demand for it in their jurisdiction. Similarly to other studies, officers report that the training gave them an increased sense of confidence when taking crisis calls (Borum et al, 1998;Canada, Angell, & Watson, 2012;Hanafi et al, 2008;Heilbrun et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interviews with officers revealed that they frequently self-select into CIT training because of prior experience with someone who had mental illness (Cross et al, 2014;Wood & Watson, 2017) or they believed they would benefit from having the enhanced skills as a response to the demand for it in their jurisdiction. Similarly to other studies, officers report that the training gave them an increased sense of confidence when taking crisis calls (Borum et al, 1998;Canada, Angell, & Watson, 2012;Hanafi et al, 2008;Heilbrun et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Studies of the impact of CIT training on officers found that they report increased confidence in their approach with individuals who exhibit symptoms of mental illness (Borum, Deane, Steadman, & Morrissey, 1998;Hanafi, Bahora, Demir, & Compton, 2008;Heilbrun et al, 2012) and perceive themselves as more efficacious at serving this population (Borum et al, 1998). Additionally, CIT-trained officers show significant increases in their knowledge of symptoms of mental illness and exhibit a change in attitude toward this population (Compton, Esterberg, McGee, Kotwicki, & Oliva, 2006;Hanafi et al, 2008;Wells & Shafer, 2006).…”
Section: Impact Of Citsmentioning
confidence: 99%
“…Additionally, there is wide acknowledgement of the overrepresentation of persons with mental illnesses in jails and prisons, and the need to divert them from the criminal justice system at the earliest point possible, ideally at the initial point of contact with the police (Heilbrun, et al 2012; Munetz & Griffin, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…The SIM was selected as the overarching model based on the literature supporting its successful use in similar programs (Heilbrun, DeMatteo, Yasuhara, Brooks-Holliday, Shah, King, et al, 2012;Kelsey, 2004;NIMH SBIR, 2005;OMHSAS, 2002). Delaware had also used the SIM previously in the design of their mental health court (DE Supreme Court, 2010).…”
Section: Sequential Intercept Modelmentioning
confidence: 99%